The University Library of Leuven historical walking tour - Van Impe, Jan 1958- (Lipsius, 2012)
Updated pocket guide with history, architecture, biographical notes and a walking tour in and around the library. The University Library at the Mgr. Ladeuzeplein in Leuven is not only a beautiful building and a modern scientific library consulted by more than 100,000 readers a year, but also an important historical monument. Its foundations are rooted in that tragic episode in the 20th century, the First World War. In the mass destruction of Leuven in 1914 the library of the University was burned and completely destroyed. Thanks to generous American donations the new library building on the Mgr. Ladeuzeplein was established in 1921